Optimalisasi penggunaan smartphone pribadi untuk mendukung aktivitas olahraga aman dan terukur pada siswa sekolah menengah pertama - Yudhi Teguh Pambudi; Topo Suhartoyo; Abdul Malik Firdaus; Mukhammad Miftakhul Farkhan (Darmabakti: Jurnal Pengabdian kepada Masyarakat, 2026)
The high smartphone ownership among junior high school students in Banyumas Regency (99%) has not been matched by their use to support physical fitness. The majority of device use is limited to entertainment (games or social media), and smartphone ownership has not been fully leveraged for its functions or its role in supporting physical activity. This community service program aims to educate and train students and teachers in utilizing smartphone-based sports applications to support higher-quality physical activity. The activity was carried out in partnership with the Subject Teacher Working Group (MGMP) Physical Education, Sports, and Health (PJOK) Junior High School (SMP) Sub Rayon 06 Banyumas, involving 16 teachers and 547 students. The implementation methods included socialization, training in the implementation of the Strava (performance monitoring) and IQAir AirVisual (environmental air quality monitoring) applications, and monitoring and evaluation. The activity results showed significant behavioral changes, with 99% of participants adopting the technology. This program successfully transformed smartphones from mere entertainment devices into health-tech tools, improved students' digital literacy, and created a safe, measurable, and data-driven sports culture in the school environment.